Ensino de automação utilizando kit FPGA DE2 modelo 2C35 da Altera - LISBOA, Ricardo Freitas (2023)
This work presents a set of practical guides for teaching Automation and Control En gineering using Programmable Logic Devices (PLDs), specifically Field Programmable Gate Arrays (FPGAs). The methodological proposal is based on the use of simulation tools and computer-aided design for teaching automation in the Electrical Engineering course, involving interdisciplinary projects and active and collaborative learning practices. Firstly, a study of the basic concepts of the VHDL language (VHSIC Hardware Description Language, where VHSIC stands for Very High Speed Integrated Circuit) and the basic characteristics of FPGA devices is presented. This approach aims to provide students with a solid theoretical understanding and the ability to design and implement digital circuits using this language and technology. The practical guides provided in this work are a valuable tool to assist in the effective and practical teaching of Automation and Control Engineering, empowering students to acquire the necessary skills in this field.